Comparison of numerical approaches for structural response analysis of passenger ships in collisions and groundings. (January 2022) - Kim, Sang Jin; Taimuri, Ghalib; Kujala, Pentti; Conti, Fabien; Le Sourne, Hervé; Pineau, Jean-Philippe; Looten, Thibaut; Bae, Hongseok; Mujeeb-Ahmed, M.P.; Vassalos, Dracos; Kaydihan, Levent; Hirdaris, Spyros
Abstract: The dynamic response of ships following grounding and collision accidents may be influenced by structural topology as well as operational and environmental conditions. Traditionally, the consequences of such events may be assessed by crude empirical methods or laborious experiments. Computational methods offer a useful alternative in terms of accurately capturing crushing mechanisms also accounting the influence of surrounding water. This paper presents a benchmark study that compares the structural dynamic response by explicit nonlinear FEA approaches and the semi-numerical super-element method. Simulations for typical accident scenarios involving passenger ships confirm that implementing the influence of hydrodynamic restoring forces in way of contact may be useful for either collision or grounding. Yet, for grounding scenarios, the damaged area resulting from analytical simulations appears to be sensitive to the failure strain values adopted to model the rupture of the ship bottom floors. Highlights: Explicit nonlinear FSI methods utilising FEA and super element methods are benchmarked for various scenarios. Structural topology, operational scenarios and environmental conditions influence accidental wave loads uncertainties. Hydrodynamic restoring forces affect both collision or grounding loads. In grounding breach sizes are sensitive to failure strain values. Comparisons demonstrate that the super element method may be used for regulatory development.